Relationship Between Serum Osteocalcin Levels and Glycosylated Hemoglobin in Type II Diabetes Patients: Osteocalcin Levels and Glycosylated Hemoglobin in Diabetes Patients - Mufti, Maria; Khaliq, Nida; Munir, Mehtab; Khattak, Almas; Mufti, Arsalan; Ansari, Fakeha; Hassan, Bilqis; Ansar, Farrukh (Pakistan Journal of Health Sciences, 2022)
Diabetic osteopathy is a complication of diabetes that elevates the risk of bone fractures and influences bone remodeling. Osteocalcin is a bone protein produced by osteoblasts that plays a role in the regulation of glucose and energy metabolism. Objectives: To explore the relationship between the level of glycosylated hemoglobin (HbA1c) and osteocalcin in diabetic patients. Methods: This cross-sectional analytical study was carried out at Hayatabad Medical Complex, Peshawar from January 2017 to February 2018. A total of 100 patients suffering from Type 2 Diabetes Mellitus (T2DM) were recruited. HbA1c and osteocalcin levels were measured by the enzymatic method and electrochemiluminescence immunoassay, respectively. SPSS was utilized for data entry and analysis; Pearson’s correlation was performed to assess the relationship between variables while statistical significance was accepted at p < 0.05. Results: The mean (SD) age of participants was 50 (9.2), while 58% of the study population was female. The mean (SD) HbA1c and osteocalcin levels were 11.3 (8.8) and 13.1 (6.8), respectively. The results of the correlation analysis yielded a negative relationship between HbA1c and osteocalcin levels (r =-0.099), but the results were statistically non-significant (p-value =0.328). Conclusion: Our study suggested that osteocalcin level has a negative correlation with HbA1c level in Type 2 Diabetes Mellitus patients